The potential of renewable energy sources in Java Island: a systematic literature review - Fatah Kurniawan; Achmad Samsudin; Endang Sriwati; Bayram Coştu (Institute for Advanced Science Social, and Sustainable Future, 2023)
This study aims to reveal the various renewable energy sources that have the potential to be developed on the island of Java, Indonesia. Because it is cheap and easy to reach, non-renewable energy is widely used as a source of energy for people's lives. The negative side of non-renewable energy sources forces local governments to look for alternative energy sources that are more environmentally friendly. Environmentally friendly alternative energy is rarely studied, specifically on the island of Java, through literature studies. Therefore, this study used a research method: a literature study on 28 Scopus, WoS, and Sinta-indexed articles. This literature study yields the information that 10 types of renewable energy sources have the potential to be developed in Java. These renewable energy sources can be further developed using technology according to their potential in each province. Thus, this research has succeeded in linking various renewable energy sources that have the potential to be developed on the island of Java.